Pengaruh Senam Kaki terhadap ABI Penderita DM di Wilayah Kerja Puskesmas Karanganyar - Melati, Putri Sovia; Marni, Marni; Yudhianto, Kresna Agung (Universitas Muhammadiyah Klaten, 2025)
Background: Diabetes Mellitus (DM) is a chronic disease that has the potential to cause serious complications, one of which is peripheral circulation disorders that can lead to diabetic ulcers and even amputation. Early detection of circulatory disorders can be done through the Ankle Brachial Index (ABI) examination. One of the non-pharmacological interventions that is useful in improving blood circulation in the lower extremities is diabetic foot exercises. Objective: to determine the effect of diabetic foot exercises on changes in ABI values in DM patients. Method: The study used a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 76 respondents with DM in the working area of the Karanganyar Community Health Center. The intervention in the form of foot exercises was given three times in two weeks, while the ABI examination was carried out using a manual sphygmomanometer according to standard procedures. Results: The results of univariate data analysis used frequency distribution, while bivariate analysis was carried out using the Paired t-test and Wilcoxon test. The results of the Wilcoxon test showed a p-value of 0.000 (p <0.05), so Ha was accepted and Ho was rejected. This indicates a significant effect of diabetic foot exercises on improving ABI values in DM patients. Conclusion: Diabetic foot exercises have been shown to be effective in improving peripheral blood circulation and increasing ABI values in DM patients. This intervention can be recommended as a simple, inexpensive, and easy-to-implement non-pharmacological method to prevent foot complications, including diabetic ulcers and amputations.